Inflammation is a target of medical treatment for lower urinary tract symptoms associated with benign prostatic hyperplasia - De Nunzio, Cosimo (World J Urol, 2020)
PURPOSE: To review the role of a persistent prostatic inflammatory status (PIS) in the development and progression of benign prostatic hyperplasia (BPH) associated with lower urinary tract symptoms (LUTS) and which medical therapies approved for LUTS/BPH may reduce persistent PIS. METHODS: Literature search in PubMed up to July 2019. RESULTS: The cause of histologically defined persistent PIS or chronic prostatic inflammation is multifactorial. It is evident in many men with LUTS/BPH, particularly in older men and in men with a large prostate volume or more severe (storage) LUTS. Additionally, persistent PIS is associated with an increased risk of acute urinary retention and symptom worsening. Of medical therapies approved for LUTS/BPH, the current evidence for a reduction of persistent PIS is greatest for the hexanic extract of Serenoa repens (HESr). This treatment relieves LUTS to the same extent as α(1)-adrenoceptor antagonists and short-term 5α-reductase inhibitors. Limited evidence is available on the effect of other mainstream LUTS/BPH treatments on persistent PIS. CONCLUSIONS: Persistent PIS plays a central role in both the development and progression of LUTS/BPH. In men with LUTS/BPH who have a high chance of harbouring persistent PIS, HESr will not only improve LUTS, but also reduce (underlying) inflammation. Well-designed clinical studies, with a good level of evidence, are required to better evaluate the impact of BPH/LUTS medical therapies on persistent PIS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00345-020-03106-1) contains supplementary material, which is available to authorized users.